Impact of cognitive performance on disease-related knowledge six months after multi-component rehabilitation in patients after an acute cardiac event. (29th August 2020) - Salzwedel, Annett; Heidler, Maria-Dorothea; Meng, Karin; Schikora, Martin; Wegscheider, Karl; Reibis, Rona; Völler, Heinz
Abstract: Background: Although associations between cardiovascular diseases and cognitive impairment are well known, the impact of cognitive performance on the success of patient education as a core component of cardiac rehabilitation remains insufficiently investigated so far. Design: Prospective observational study in two inpatient cardiac rehabilitation centres between September 2014 and August 2015 with a follow-up six months after cardiac rehabilitation. Method: At admission to and discharge from cardiac rehabilitation, the cognitive performance of 401 patients (54.5 ± 6.3 years, 80% men) following an acute coronary syndrome and/or coronary artery bypass graft was tested using the Montreal Cognitive Assessment. Patients' disease-related knowledge was determined using a quiz (22 items for medical knowledge and 12 items for healthy lifestyle and behaviour) at both times and at follow-up. The change in knowledge after cardiac rehabilitation was analysed in multivariable regression models. Potentially influencing parameters (e.g. level of education, medication, cardiovascular risk factors, coronary artery bypass graft, comorbidities, exercise capacity) were considered. Results: During cardiac rehabilitation, disease-related knowledge was significantly enhanced in both scales. At follow-up, the average level of medical knowledge was significantly reduced, while lifestyle knowledge remained at a stable level. The maintenance of knowledge after cardiac rehabilitation was predominantly predicted by prior knowledge, cognitive performance at discharge from cardiac rehabilitation and, in the case of medical knowledge, by coronary artery bypass graft. Conclusion: Patient education in cardiac rehabilitation led to enhanced disease-related knowledge, but the maintenance of this essentially depended on patients' cognitive performance, especially after coronary artery bypass graft. Therefore, patient education concepts in cardiac rehabilitation should be reconsidered and adjusted as needed.